Effect of quercetin on histamine induced gastric ulcers in male guinea pigs - Narayanamurthy, Uma; Jayachandran, Ranjani; Ramarajan, Sudar Codi; Kumarappan, Manimekalai; R., Kanan; D., Barathane (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Peptic ulcer disease is the most prevalent gastrointestinal diseases caused by an imbalance between gastric stimulant or aggressive factors and the mucosal defensive factors. The defence of flavonoids against the tissue oxidative stress is being proved in various animal models for wide pharmacological effects. The aim of the present study is to evaluate the anti-oxidant effect of quercetin in histamine induced gastric ulcers. Methods: Male guinea pigs were divided into 4 groups (n=6). Group I includes normal control. Group 2, 3 and 4 were induced gastric ulcers with histamine as intraperitoneal (IP) injection. Group 2 serves as the gastric ulcer control. Group 3 and Group 4 are pre-treated with quercetin 200 mg/kg per orally (PO) and ranitidine 100 mg/kg PO respectively 45mins before histamine injection. After 4 hours of histamine injection, the animals were sacrificed to collect blood samples and stomach tissue for estimation of plasma and tissue antioxidant levels. Results: On estimation of antioxidant levels both in plasma and stomach tissues the SOD and CAT levels increased in the Group 3 and 4 significantly and also a significant reduction in MDA levels were noted in the Group 3 and 4 compared to the gastric ulcer control group. Conclusions: Hence, with flavonoids quercetin utilization in histamine induced gastric ulcers, the antioxidants showed comparative levels with ranitidine treatment groups. So a permanent cure for the chronic gastric ulcers could be proved in further studies as this is the milestone, tough to achieve in general clinical practice.